Revision of Reporting Insurance Events in the Company ING Životní Pojišťovna N.V. - Navrátilová, Tereza (2012)
The aim of my thesis is to clarify several processes in the settlement of claims in ING Life Insurance NV, Czech Republic branch, the analysis of the current situation of reporting claims, processing, analysis, presenting some recommendations for improvement of the current situation. Another goal of my diploma thesis is to present the project eLikvidace (eClaims), which helped to simplify the reporting claims and evaluating the benefits of the project. The work is divided into three main chapters. The first is theoretical and the two others are more practical. The contribution of this thesis is the claryficitaion of the processes regarding the reporting of claims, the presentation of the project and evaluation of its benefits for the company and for the clients.